Factors influencing the intention of financial managers to conduct whistleblowing action (A study on the Government of Kotamobagu City) - Fahmi, Abdul Rahim; Tinangon, Jantje J.; Manossoh, Hendrik (Yayasan Widyantara Nawasena Raharja, 2024)
This study aims to analyze the factors influencing the intention of financial managers to engage in whistleblowing within the Kotamobagu City Government. Using an associative quantitative research method, data were collected via questionnaires. The population for this study comprises financial managers within the Kotamobagu City Government. Data analysis was conducted using partial least squares (PLS) to determine the influence of each variable on the intention on whistleblowing. The results indicate that whistleblower protection, ethical judgment, and organizational commitment have a positive and significant impact on the intention of financial managers to engage in whistleblowing. Conversely, ethical climate, locus of control, level of seriousness of wrongdoing, and status of wrongdoer do not show significant effects. The variables of gender, age, and tenure also do not significantly influence whistleblowing intentions. These findings suggest that adequate protection for whistleblowers, good ethical judgment, and strong organizational commitment can encourage financial managers to report illegal or unethical actions. This study is expected to contribute to the development of government policies and organizational practices that support a conducive environment for whistleblowing and provide protection for whistleblowers.